The Value of Ocular Ultrasound in Monitoring Intracranial Pressure in Patients with Ventricular Drains: A Preliminary Longitudinal Study (Vietnam Journal of Community Medicine, 2026)
Background: Intracranial pressure (ICP) monitoring is essential in neurocritical care, yet invasive techniques remain the gold standard despite associated risks. Ocular ultrasonography, particularly optic nerve sheath diameter (ONSD), has emerged as a promising non-invasive surrogate, although longitudinal data remain limited. Aim: To preliminarily evaluate the role of ocular ultrasonography in monitoring ICP dynamics in patients undergoing external ventricular drainage.Methods: A prospective longitudinal study was conducted on 7 patients with intracranial hypertension requiring external ventricular drainage. ONSD, optic disc elevation (ODE), and posterior globe flattening were assessed at multiple time points and compared with invasively measured ICP. Correlation between ONSD and ICP was analyzed using Linear Mixed-Effects Models’s correlation coefficient. Results: ICP significantly decreased from 24.86 ± 3.93 to 6.86 ± 1.86 mmHg (p < 0.001), accompanied by a reduction in ONSD from 5.96 ± 0.51 to 5.05 ± 0.11 mm (p = 0.002). Analysis of 32 longitudinal measurements demonstrated a strong positive correlation between ONSD and ICP (r = 0.802; p < 0.001). ONSD generally paralleled ICP changes but exhibited a time-lag during ICP reduction. A case of ICP–ONSD mismatch was observed. ODE showed low sensitivity (28.5%) and delayed normalization, while posterior globe flattening was not detected.Conclusion: Ocular ultrasonography is a valuable non-invasive tool for monitoring ICP dynamics, with ONSD showing strong correlation with invasive ICP measurements. However, clinicians should consider the time-lag phenomenon and potential mismatch in interpretation. Larger studies are warranted to establish optimal cut-off values and clinical applicability.
Keywords: Ocular ultrasonography; optic nerve sheath diameter; intracranial pressure; external ventricular drainage; longitudinal monitoring.